IDENTIFIKASI HIDROKUINON DALAM KRIM PEMUTIH DENGAN METODE KROMATOGRAFI LAPIS TIPIS (KLT) - NI NYOMAN YULIANI; SRI WIDIAYATI DJOU (JURNAL INFO KESEHATAN, 2014)
Has done research on the identification of hydroquinone bleaching creams with brand wallet and kelly circulating in Kupang by thin layer chromatography method in Laboratory Cosmetics And Traditional Medicinal Drug and Food Control Center Kupang. The purpose of this study was to determine whether there is hydroquinone in whitening creams in Kupang. The method used in this research is thin layer chromatography, where the value of the sample compared Rf Rf value of raw materials. If the Rf value of the sample and the same raw material, the positivecontaining hydroquinone. From the results obtained show that the price of Rf of cream bleach with Swallow and Kelly brand different from the value of Rf hydroquinone. So it can be concluded that the two samples tested all showed negative results that do not contain hydroquinone.